Cost-Utility Study of the Economics of Bunion Correction Surgery. (March 2019) - Sutherland, Jason M.; Mok, Janice; Liu, Guiping; Crump, Trafford; Wing, Kevin; Younger, Alastair; Penner, Murray; Veljkovic, Andrea
Background: Bunion correction surgery is a very common procedure to improve patients' pain and physical function attributable to a misaligned first metatarsophalangeal joint. The objective of this study was to apply a health utility framework to estimate the cost utility of bunion correction surgery. Methods: Patients were prospectively recruited from the population of patients seen in a lower-extremity orthopedic clinic and scheduled for isolated bunion surgery. Participants completed EuroQoL's EQ-5D(3L) to measure patients' current general health preoperatively and 6 months postoperatively. Participants' change in quality-adjusted life years (QALYs) were calculated by comparing the difference between postoperative utility values and preoperative utility values. The study had 95 patients representing 53% of eligible patients. Results: The mean preoperative utility value was 0.6816 and the mean postoperative value was 0.7451, a statistically significant difference denoting an improvement in self-reported health. The cost per QALY, assuming gains in health accrued for 15 years, was 4911 (the 95% confidence interval ranged from 4736 to 5088). The cost per QALY was highest among the oldest patients. Assuming gains in health accrued for 20 years, the cost per QALY was 3922. Conclusion: This study demonstrated that bunion correction surgery was inexpensive relative to its gains in health compared with commonly applied thresholds for women and men in all age groups, though the gains were not uniformly distributed across age categories. Future research should examine the impact of recurrence on the robustness of these findings. Level of Evidence: Level III, comparative study.